Proposed interior design scheme of children’s library entertainment & education area for Mid Valley Management at Mid Valley Megamall, Persiaran Syed Putra, 52900, Kuala Lumpur / Muhammad Nor Halim Mukhlas - Mukhlas, Muhammad Nor Halim (Faculty of Architecture, Planning and Surveying, 2011)
This report is on Proposed Interior Design Scheme Of Children’s Library Entertainment & Education . The suggested location at Mid Valley Megamall, Persiaran Syed Putra , 52900 , Kuala Lumpur. This is peject report of children’s library at Mid Valley Megamall. Children’s library is important for each children’s because with the children’s library can learn lot of things , apart can learn , play while learning , know a lot of friends , children’s can also us the spare time to learn than by their parents go to shopping . Nowdays problems on children’s library is also often said , is the lack of children’s library in shopping complex . Government campaigns for children’s to read in order to attract themto reading , in addition with children’s library can create a special space for them to make a usefull things such as reading . Valuable time can also be used to correct than on go to shopping with paret’s . The objective of doing project report is to give student a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language .This course will make student practice to do some research based on their project proposal at part six(06). Student also should fulfill all the requirement needed and must follow the stage. Library is a collection information , sources , resources , and services , and the structure in which it is housed, it is housed it is organized for use and maintained by a public body , an institution , or a private individual I. In the more traditional sense, a library is a collection of books . The term can mean the collection, the building that houses such a collection, or both. Children of all ages should find the library an open, inviting, attractive, challenging and non-threatening place to visit. Children’s library contain an book, extreme activity , entertainment and many more. In this paper we describe the meaning of library, services, space requirement at library such as information gathered by site analysis , interviews , books , case studies and etc . The focus is design a library that is functional, attractive children’s interests , better usual library in Malaysia.